Path analysis in Mplus: A tutorial using a conceptual model of psychological and behavioral antecedents of bulimic symptoms in young adults - Barbeau, Kheana; Boileau, Kayla; Sarr, Fatima; Smith, Kevin (Tutorials in quantitative methods for psychology, 2019)
Path analysis is a widely used multivariate technique to construct conceptual models of psychological, cognitive, and behavioral phenomena. Although causation cannot be inferred by using this technique, researchers utilize path analysis to portray possible causal linkages between observable constructs in order to better understand the processes and mechanisms behind a given phenomenon. The objectives of this tutorial are to provide an overview of path analysis, step-by-step instructions for conducting path analysis in Mplus, and guidelines and tools for researchers to construct and evaluate path models in their respective fields of study. These objectives will be met by using data to generate a conceptual model of the psychological, cognitive, and behavioral antecedents of bulimic symptoms in a sample of young adults.